Siasat Kebudayaan Komunitas Adat Dayak Lepoq terhadap Kebijakan Pelarangan Membakar Lahan di Desa Lung Anai Kecamatan Loa Kulu Kabupaten Kutai Kartanegara - Dini, Wa; Arifin, Muhammad (Sasdaya: Gadjah Mada Journal of Humanities, 2024)
This study focused on the cultural strategies of the Dayak Kenyah traditional community in Lung Anai Village in farming practices as a response to the government policy concerning controlling forest and land burn. The cultural strategy referred to was a social practice related to the management and utilization of local resources, including the practice of local wisdom in farming in the form of burning which is passed down from one generation to the next. The research method that the researcher used was a type of qualitative descriptive research with data collection carried out by means of observation and in-depth interviews. The findings from this research were that the response of the Dayak Kenyah Lung Anai to the policy of prohibiting land burning was very diverse. The public responded to this policy in two ways, namely attitudes and actions. Their attitude was gossip and the actions of the community were carrying out one-time demonstrations. The Lung Anai community had a closed resistance, namely burning in the afternoon until evening, providing barriers, asking companies for help, using village land, increasing income. The conclusion of this research is that the cultural tactics carried out is a form of resistance by indigenous communities to government policies in order to survive by maintaining their traditions in the practice of managing and utilizing local resources.